KUALITAS PELAYANAN ADMINISTRASI PADA PEMERINTAH DESA GEGUNUNG WETAN KECAMATAN REMBANG KABUPATEN REMBANG - Nururrohmah, Nururrohmah; Yuniningsih, Tri; Djumiarti, Titik (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Public services have always been a benchmark for concrete government performance standards. It is known that the Gegunung Wetan Village Government has limitations in terms of poor service due to inadequate service facilities, unclear information and SOPs, and passive mechanisms for handling aspirations and suggestions due to a lack of use of digitalization. The aim of this research is to describe the quality of public services in the Gegunung Wetan Village Government and identify the driving and inhibiting factors of these services. The type of research used is descriptive qualitative with data collection methods in the form of interviews, observation, documentation and literature study. The research results show that only the empathy dimension has been implemented optimally. Meanwhile, the tangible dimension, reliability dimension, responsiveness dimension and assurance dimension are still not optimal in implementation. So the services from the Gegunung Wetan Village Government still have polemics which have an impact on the lack of satisfaction from residents. The driving factors for the formation of optimal service q”alit’In the Gegunung Wetan Village Government come from organizational factors and income factors, while factors that inhibit this are awareness factors, regulatory factors, ability and skill factors, and service facilities factors.